Pectin methylesterase 31 is transcriptionally repressed by ABI5 to negatively regulate ABA-mediated inhibition of seed germination - Xiang, Yang; Zhao, Chongyang; Li, Qian; Niu, Yingxue; Pan, Yitian; Li, Guangdong; Cheng, Yuan; Zhang, Aying (Frontiers in Plant Science, 2024)
Pectin methylesterase (PME), a family of enzymes that catalyze the demethylation of pectin, influences seed germination. Phytohormone abscisic acid (ABA) inhibits seed germination. However, little is known about the function of PMEs in response to ABA-mediated seed germination. In this study, we found the role of PME31 in response to ABA-mediated inhibition of seed germination. The expression of PME31 is prominent in the embryo and is repressed by ABA treatment. Phenotype analysis showed that disruption of PME31 increases ABA-mediated inhibition of seed germination, whereas overexpression of PME31 attenuates this effect. Further study found that ABI5, an ABA signaling bZIP transcription factor, is identified as an upstream regulator of PME31. Genetic analysis showed that PME31 functions downstream of ABI5 in ABA-mediated seed germination. Detailed studies showed that ABI5 directly binds to the PME31 promoter and inhibits its expression. In the plants, PME31 expression is reduced by ABI5 in ABA-mediated seed germination. Taken together, PME31 is transcriptionally inhibited by ABI5 and negatively regulates ABA-mediated seed germination inhibition. These findings shed new light on the mechanisms of PMEs in response to ABA-mediated seed germination.